2018
DOI: 10.1111/nyas.13606
|View full text |Cite
|
Sign up to set email alerts
|

Music training and child development: a review of recent findings from a longitudinal study

Abstract: Evidence suggests that learning to play music enhances musical processing skills and benefits other cognitive abilities. Furthermore, studies of children and adults indicate that the brains of musicians and nonmusicians are different. It has not been determined, however, whether such differences result from pre-existing traits, musical training, or an interaction between the two. As part of an ongoing longitudinal study, we investigated the effects of music training on children's brain and cognitive developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
1
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(83 citation statements)
references
References 53 publications
0
73
1
9
Order By: Relevance
“…The present study intends to update Sala and Gobet's (2017b) meta-analysis and test the recent claims about the presumed cognitive and academic benefits of music training (e.g., Habibi et al, 2018). To achieve this goal, we (a) extend the literature research to the last three years (from January the 1 st 2016 to December the 31 st 2018), (b) apply a more advanced modeling approach, and (c) provide stricter inclusion criteria to improve, compared to Sala and Gobet (2017b), the average quality of the studies included in the meta-analytic review.…”
Section: Experimental Evidence and Present Studymentioning
confidence: 96%
“…The present study intends to update Sala and Gobet's (2017b) meta-analysis and test the recent claims about the presumed cognitive and academic benefits of music training (e.g., Habibi et al, 2018). To achieve this goal, we (a) extend the literature research to the last three years (from January the 1 st 2016 to December the 31 st 2018), (b) apply a more advanced modeling approach, and (c) provide stricter inclusion criteria to improve, compared to Sala and Gobet (2017b), the average quality of the studies included in the meta-analytic review.…”
Section: Experimental Evidence and Present Studymentioning
confidence: 96%
“…). Improvements due to musical training can be observed for a variety of perceptual and cognitive tasks, including speech‐in‐noise perception, auditory selective attention, and executive functions …”
Section: Musical and Verbal Short‐term Memory In Healthy Individualsmentioning
confidence: 99%
“…Improvements due to musical training can be observed for a variety of perceptual and cognitive tasks, including speech-in-noise perception, 31 auditory selective attention, 32 and executive functions. 33 A meta-analysis of studies comparing STM and WM (as well as LTM) in musicians and nonmusicians was recently performed. 34 It confirmed that musicians perform better than nonmusicians in memory tasks.…”
Section: Effects Of Expertise On Musical and Verbal Shortterm Memorymentioning
confidence: 99%
“…From an "Il Sistema"-based intervention (http://sistema-toronto.ca/), we now know that it also facilitates sound-related neural functions in 2 years from the project onset. Such facilitation is not observed after a sport-based intervention, or in control children (Habibi et al, 2016(Habibi et al, , 2017; for a review see Habibi et al, 2018).…”
Section: Studies In Community Settingsmentioning
confidence: 99%